Soft Iontronics: AI-Based Self-Regulating Energy Storage in Living Tissues - Dusi, Prerna; Tiwari, Ankita; Desai, Tripti (Malikussaleh University, Aceh, Indonesia, 2025)
Using Soft iontronics as a revolutionary approach for biocompatible energy storage is impossible without next-generation biomedical implants and bioelectronic systems. The proposed soft iontronic energy storage system dynamically regulates itself, based on physiological conditions, as an AI-driven, with the capability of efficient energy management in living tissues. Using ionic hydrogels as supercapacitors, and based on AI-powered adaptive power distribution, the system uses biocompatible supercapacitors for stable and flexible charge storage under real-time conditions. Bioenergy harvesting mechanisms, which are integrated in the device, are enzymatic biofuel cells and piezoelectric nanogenerators that allow continuous power generation, thereby reducing the dependence on external charging. With a predictable AI model which fine-tunes the energy release to match the cellular demands, implant longevity and associated energy losses are improved. To confer durability and long-term integration into biological environments, the framework is proposed to include self-healing polymer networks. The superior energy efficiency, rapid charge-discharge cycles, high biocompatibility, and performance evaluations are compared to standard bioelectronic energy systems. The applications from neuro interfaces, cardiac implants, and smart prosthetics are potential, which represent a major advancement in bio-integrated power solutions. The results provide a blueprint for the transition from living tissues to cleverly intelligent bioelectronic devices and the gap between the two. In future work, we will enlarge scalability, real-time optimisation, and in vivo testing to make the practical applicability.